Astragaloside IV Relieves Atherosclerosis and Hepatic Steatosis via MAPK/NF-κB Signaling Pathway in LDLR−/− Mice - Zhang, Yifan; Du, Min; Wang, Jiarou; Liu, Ping (Frontiers in Pharmacology, 2022)
Astragaloside IV (AS-IV) is the main active compound of Astragalus membranaceus. In this study, we investigated whether AS-IV could attenuate atherosclerosis and hepatic steatosis in LDLR-/-mice and its potential mechanisms. After 12 weeks of high fat diet, the LDLR-/-mice were randomly divided into four groups. Then, the mice were administrated with 0.9% saline or AS-IV (10 mg/kg) or atorvastatin (1.3 mg/kg) for 12 weeks. Serum lipid profiles and inflammatory cytokines were detected by ELISA, hepatic TC and TG by colorimetric enzymatic kits, gene expression by RT-qPCR, plaque sizes by H&E staining, Oil Red O, liver pathology by H&E staining, collagen content by Masson, α-SMA, caspase-3 and NF-κB p65 production by immunofluorescence staining. MAPK/NF-κB pathway and inflammation related proteins were detected by Western Blot. The results showed that AS-IV decreased the levels of serum lipids, reduced plaque area and increased plaque stability in HFD-induced LDLR-/- mice. AS-IV also decreased the levels of inflammatory cytokines in the serum, aortas and liver tissue, and NF-κB p65 in aortic roots. The phosphorylation of JNK, ERK1/2, p38 and NF-κB, and inflammatory proteins (iNOS, VCAM-1and IL-6) was inhibited in AS-IV-treated group. In summary, AS-IV inhibited inflammation to attenuate atherosclerosis and hepatic steatosis via MAPK/NF-κB signaling pathway in LDLR-/- mice.